ANALISIS FORMULASI STRATEGI BISNIS DALAM MENGAHADAPI PERSAINGAN INDUSTRI DOORSMEER (Kasus: Penerapan Analisis SWOT pada Ritonga Doorsmeer Duri-Riau) - Salimukdin, Johan; Karneli, Okta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study was conducted in Ritonga Doorsmeer thorns. This business is engaged in vehicle wash services. The purpose of this study is to formulate business strategies in Ritonga Doorsmeer.This research is a descriptive qualitative approach which in this study did not use the sample population only uses key informants to obtain the required information. The data used are primary and secondary data.From the analysis it can be seen that there are some alternative strategies that can be used as a tool to win the competition in the industry doorsmeer Ritonga. And the results of this analysis to formulate long-term strategies.Keywords: SWOT (Strengths, Weakness, Opportunity, Threat), SWOT Analysis, Alternative Strategies Ritonga Doorsmeer